Social and self-stigma in alcohol and drug addiction among women - Atlam, Demet; Çınaroğlu Asar, Ayça; Şaşman Kaylı, Derya; Kırlı, Umut (Journal of Dependence, 2024)
Addiction is a chronic mental illness in which biological, psychosocial and environmental factors play a role. Gender is an important factor in addiction, and women experience the process of addiction differently compared to men. By this review, it is aimed to draw attention to the difference in the addiction process of women, the social stigma towards women and the psychosocial elements that may play a role in self-stigma of the women. Society’s evaluation of men and women also differs in addiction. Society’s more prejudiced approach to female patients also exacerbate women’s self-stigma. The increased severity of self-stigma leads to greater shame, guilt, loneliness, decreased self-esteem, depression, social isolation, and treatment avoidance. Referring to the woman’s mother role and the process of caregiving to children also play a role on treatment avoidance. Individuals who stigmatize themselves try to cope with this process unconsciously by using the substance they are addicted to. This situation may hamper to get out of the addiction cycle. In conclusion, in order to reduce self stigma, it is necessary to increase social awareness on addiction, reduce social stigmatization, ensure women’s access to treatment, support the treatment process with psychotherapies and social therapies, create employment opportunities and childcare processes for the women, strengthen social support networks of the women.